2020
DOI: 10.3389/fped.2020.00450
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler Can Predict Development and Outcome of Sepsis-Associated Encephalopathy in Pediatrics With Severe Sepsis or Septic Shock

Abstract: Background and Aim: Sepsis is a common cause of pediatric intensive care unit (ICU) admission. Sepsis-associated encephalopathy (SAE) may occur owing to brain dysfunction in those patients and may be related to impaired cerebral microcirculation. Transcranial Doppler (TCD) can be used to detect this impairment. In this study, we aimed to assess the role of TCD in prediction of SAE and mortality in patients with severe sepsis or septic shock admitted to PICU. Patients and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The association between severe sepsis and septic shock and increased cerebral vascular resistance as assessed by TCD estimated pulsatility index (PI) and resistance index (RI) was previously reported (PI = systolic velocity-(diastolic velocity/mean velocity); RI = systolic velocity-(diastolic velocity/systolic velocity)) [26]. The study of Algebaly et al, showed that pediatric septic patients with SAE had significantly higher PI and RI than their counterparts without SAE [27].…”
Section: Cerebral Perfusion Pressure (Cpp) Under Condition Of Violate...mentioning
confidence: 83%
“…The association between severe sepsis and septic shock and increased cerebral vascular resistance as assessed by TCD estimated pulsatility index (PI) and resistance index (RI) was previously reported (PI = systolic velocity-(diastolic velocity/mean velocity); RI = systolic velocity-(diastolic velocity/systolic velocity)) [26]. The study of Algebaly et al, showed that pediatric septic patients with SAE had significantly higher PI and RI than their counterparts without SAE [27].…”
Section: Cerebral Perfusion Pressure (Cpp) Under Condition Of Violate...mentioning
confidence: 83%
“…Among these, the evaluation of pulsatility index (PI) and noninvasive estimation of intracranial pressure (e-ICP), both derived from flow velocities of major intracranial arteries (particularly the middle cerebral arteries), as well as the analysis of PI and velocity of venous flow of the superior sagittal sinus or straight sinus, have shown encouraging results. [16][17][18] Howev-er, in a study by Robba et al, which compared all these ultrasonographic methods for identifying intracranial hypertension, ONSD measured by ONUS showed the most significant correlation with invasive measurements of ICP. 19 In another study by Robba et al, e-ICP showed the best correlation with invasive ICP instead.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Algebaly et al recruited 45 children with SAE and found that PI and RI were significantly higher in SAE patients compared to their counterparts without SAE. Specifically, PI was more negatively correlated to a Full outline of unresponsiveness (FOUR) score with high significance and PI related well with illness severity when assessed by the paediatric risk of mortality assessment III (PRISM III) and hence increasing cerebrovascular resistance (CVR) with subsequent deepening of coma (Algebaly et al 2020). Similar results were also reported in SAE adult patients, where a majority of patients (76%) presented a maximum PI > 1.1, showing a lower GCS at the initiation of sepsis and indicating that a PI cut-off value of > 1.3 could be used in clinical practice as a risk factor for delirium in septic patients (Pierrakos et al 2014).…”
Section: Transcranial Dopplermentioning
confidence: 98%